QFD and Fuzzy AHP for Formulating Product Concept of Probiotic Beverages for Diabetic - Imam Santoso; Miftahus Sa’adah; Susinggih Wijana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In Indonesia, the number of diabetics is increasing. In term of age, people suffered diabetes at the age of 20-79 years old in the past, but now young people also suffer it. Some of the attempts to contain uncontrollable effects of diabetes are to implement healthy lifestyle and to control type or amount of consumed foods. One type of product to ease the risks of Type 2 Diabetes Mellitus is dairy product, and its derivatives.  One example of the product is probiotic. This research is intended to design yoghurt product for diabetic consumption, using quality function deployment (QFD) and fuzzy Analythical hierarchy process (fuzzy AHP) methods. This research shows that the technical responses, that serve the priority to develop probiotic product for diabetics, are the use of low-calorie sugar and skimmed milk, and the addition of high-fiber ingredients.